Haemophilus ducreyi Cutaneous Ulcer Strains Diverged from Both Class I and Class II Genital Ulcer Strains: Implications for Epidemiological Studies. - Dharanesh Gangaiah; Stanley M Spinola (Public Library of Science (PLoS), 2016)
Background Haemophilus ducreyi has emerged as a major cause of cutaneous ulcers (CU) in yaws-endemic regions of the tropics in the South Pacific, South East Asia and Africa. H. ducreyi was once thought only to cause the genital ulcer (GU) disease chancroid; GU strains belong to 2 distinct classes, class I and class II. Using whole-genome sequencing of 4 CU strains from Samoa, 1 from Vanuatu and 1 from Papua New Guinea, we showed that CU strains diverged from the class I strain 35000HP and that one CU strain expressed β-lactamase. Recently, the Center for Disease Control and Prevention released the genomes of 11 additional CU strains from Vanuatu and Ghana; however, the evolutionary relationship of these CU strains to previously-characterized CU and GU strains is unknown. Methodology/principal findings We performed phylogenetic analysis of 17 CU and 10 GU strains. Class I and class II GU strains formed two distinct clades. The class I strains formed two subclades, one containing 35000HP and HD183 and the other containing the remainder of the class I strains. Twelve of the CU strains formed a subclone under the class I 35000HP subclade, while 2 CU strains formed a subclone under the other class I subclade. Unexpectedly, 3 of the CU strains formed a subclone under the class II clade. Phylogenetic analysis of dsrA-hgbA-ncaA sequences yielded a tree similar to that of whole-genome phylogenetic tree. Conclusions/significance CU strains diverged from multiple lineages within both class I and class II GU strains. Multilocus sequence typing of dsrA-hgbA-ncaA could be reliably used for epidemiological investigation of CU and GU strains. As class II strains grow relatively poorly and are relatively more susceptible to vancomycin than class I strains, these findings have implications for methods to recover CU strains. Comparison of contemporary CU and GU isolates would help clarify the relationship between these entities.